A Survey of Stochastic processes in Wireless Sensor Network: a Power Management Prospective - Ul haq, Riaz; Norrozila, Sulaiman; Muhammad, Alam (2013)
A wireless sensor network consist of large number of low cost, low computational and limited power sensors. Routing is a process which consumes lot of WSN nodes power. On the other hand WSN nodes have limited power, therefore it is required to intelligently design and select the routing algorithm for the WSN field. This will increase the node and the network life. Statistical tools are quite famous for the decision making procedure in artificial intelligence, self-learning and neural network. A huge research has been done in the recent era on power management and energy efficient protocols to improve the efficiency of the WSN. This survey is focusing on the stochastic process based power management algorithms for the WSN field. Famous power efficient routing algorithms hierarchical structures and format are discussed in this survey